Exploração de modelos agregados para distribuição de viagens urbanas : uma abordagem baseada nas oportunidades intervenientes - Lemos, Bruno Morais (2020)
The main objective of this work is to evaluate the intervening opportunities spatial distribution influence on aggregate trip distribution models. The specific objectives are based on the influence that different levels of aggregation have on some models of trip distribution; in the empirical validation of the proposal for two variations of a trip distribution model and in the testing of the models evaluated in different scenarios. The primary hypothesis tested was whether the dimension variation of the geometric shapes used to define the intervening opportunities can positively influence the forecasting capacity of the trip distribution models evaluated in this thesis. In order to achieve the objectives and test the hypotheses stated in this thesis, an experiment was carried out based on data from 697,914 passenger trips made in the city of Rio de Janeiro. This information was organized into two forms of zoning, using the geometric figures circle and ellipse, including variations in their dimensions, in defining the intervening opportunities. Together with the zoning forms and opportunities definition, 5 trip distribution models were tested, resulting in an experiment composed of 178 OriginDestiny matrices, considered as scenarios. In most of the scenarios evaluated, the results show that proposals for variations in trip distribution model and different ways of defining intervening opportunities can improve travel forecast ability.